(untitled) (REMUNOM, 2024)
Medicinal plants are producers of various metabolites and substances, among which we can mention chlorophyll, which gives the green color to plant leaves. Among the botanical genera and botanical families used in scientific experiments, the Piperaceae family and the Piper genus stand out. The genus Piper and the species Piper marginatum Jacq. which has a high chlorophyll content in its leaves, which gives them a green color and this content is often not quantified and among the techniques used to analyze the chlorophyll concentration, the UV Spectrophotometry technique stands out. -Vis. The objective of this work was to determine the chlorophyll concentration of different extracts present in Piper marginatum Jacq collected in Itacoatiara using the UV-Vis spectrophotometry technique. The leaves of Piper marginatum Jacq. were collected at UFAM Campus I in Itacoatiara and were taken to the Chemistry laboratory where they were cleaned and subjected to the extraction process separately in solvents (water and ethanol). The extracts were filtered separately and stored in an amber bottle and kept at an appropriate temperature. The extracts were subjected to different types of tests: Chlorophyll content in UV-Vis, Refractivity, Electrical conductivity and pH. The analyzes were subjected to statistical testing using the SISVAR software for the tested parameters and the absorbances were analyzed using the SciDavis software. The results obtained evaluated that the best solvent for chlorophyll extraction was ethanol, however both extracts were stable during the tests. These results are an indication that the species is stable in both solvents, however additional tests must be carried out on the species.